(3eSDhdjI eJYgO Gdfbd eJYOO GdhSGFW (B/s - (3Ydj MSf, ShRGfs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOjI(B, s, 2003)
(3eaghe Gdfbd GdOhdj ,eJYOO GdhSGFW , CKQ GSJNOGe GdJcfhdhLjG GdMOjKI Ydi eSFhhdjI eJYgO Gdfbd eJYOO GdhSGFW , cjajI MSGH GdJYhjV aj MGdI JMhjd GdHVGFY ,GdTMf Ydi SWM GdSajfI , Gdfbd HGdeHQOGJ , GdbjeI GdbGfhfjI dhKjbI Gdfbd eJYOO GdhSGFW GJaGbjI GdGee GdeJMOI ddfbd GdOhdj eJYOO GdhSGFW dSfI (B1980s
(3bGFeI GdGNJUGQGJ (B: (3U(B. 215s
Keywords: (3GdTMfs; (3Gdfbd(B-(3bhGfjf h JTQjYGJs